Marketing modernisms : : the architecture and influence of Charles Reilly. - Richmond, Peter (Liverpool University Press, 2001)
Architect, teacher, journalist, town planner and cultural entrepreneur, Sir Charles Reilly was a leading figure of the early-20th-century British architectural scene.